PENGARUH BEBAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA DINAS PEKERJAAN UMUM DAN PENATAAN RUANG KABUPATEN BUTON - Agustyawati, Dwi; Uli, Nur Zarliani; Daholu, Ahmad; Hasni, Hasni; Zakaria, Ferli (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2024)
This study aims to determine the effect of workload and work discipline on performance carried out at the Public Works and Spatial Planning Office of South Buton Regency. Data collection methods were carried out by observation, questionnaires and documentation. Respondents in this study amounted to 38 respondents. Data processing was carried out using SPSS, and analyzed the research instrument test and multiple linear regression analysis hypothesis testing. The results of this study indicate that there is a simultaneous positive and significant effect of workload and work discipline on employee performance with a significance value of 0.027 <0.05. Based on the results of the coefficient of determination test, the adjusted r value is 0.141, which means that the independent variable in this study has an influence of 14.1% on the dependent variable. Meanwhile, workload has no effect on employee performance. Work discipline has no effect on employee performance.